Potentials of antiviral therapy at patients with liver cirrhosis in an outcome of HCV-infection - E. N. Bessonova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study efficacy and complications of antiviral therapy in patients with liver cirrhosis of HCV-etiology.Material and methods. Original study included 57 patients with liver cirrhosis of HCV-etiology of A and B classes by Child-Pugh, treated in Sverdlovsk regional center of hepatology, based on «Sverdlovsk regional hospital №1» (Yekaterinburg) in 2008 to 2010. All patients were separated into two groups: the first (27 cases) received antiviral therapy (AVT), the second (30 cases) – received no AVT.Results. The most significant factor of the positive response to AVT (even transient) was presence of non-1-st genotype of the virus C. Differences in average MELD indices in studied groups of patients at the moment of the investigation onset and after its termination show, that AVT allowed to maintain the degree of severity of cirrhosis at initial level without further progression, and in some cases at achievement of the positive response to antiviral treatment, to reach certain regression of disease.Conclusions. Optimal candidates for antiviral therapy are patients of younger age with the HCV-associated liver cirrhosis of Child-Pugh A and B classes, with non 1-st genotype. At prescription of this treatment it is necessary to take into account high risk of infections development.